2010
DOI: 10.1590/s1980-57642010dn40200002
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in clinically isolated syndrome: a systematic review

Abstract: The pattern of cognitive abnormalities in multiple sclerosis (MS) has been extensively studied and well characterized. However, little is known about the cognitive involvement in patients with the clinically isolated syndrome (CIS).ObjectivesTo perform a systematic review of the results of the studies on cognitive dysfunction in CIS patients.MethodsCochrane, Lilacs, PubMed/Medline and SciELO databases were searched for studies involving patients with clinically isolated syndrome submitted to neuropsychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
(25 reference statements)
2
10
0
Order By: Relevance
“…Some recent studies have shown that CIS patients may present mild cognitive impairment, especially in processing speed and executive functions [4][5][6] . Depression and anxiety have also been found in patients with CIS but their precise prevalence in this population is still unknown [6][7][8][9] . Quality of life has been studied in patients with multiple sclerosis (MS) but there are no previous studies evaluating quality of life in patients with CIS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have shown that CIS patients may present mild cognitive impairment, especially in processing speed and executive functions [4][5][6] . Depression and anxiety have also been found in patients with CIS but their precise prevalence in this population is still unknown [6][7][8][9] . Quality of life has been studied in patients with multiple sclerosis (MS) but there are no previous studies evaluating quality of life in patients with CIS.…”
mentioning
confidence: 99%
“…Considering that CIS is associated with cognitive dysfunction, depression and anxiety, it is possible that it can affect quality of life in patients with CIS. However, quality of life in patients with CIS is still poorly understood 6,9,[13][14][15] . The present study aimed to evaluate the quality of life of patients with CIS and to evaluate potential determinants of quality of life such as cognition, depression and anxiety in patients with CIS.…”
mentioning
confidence: 99%
“…When stringent criteria are implemented, approximately 30% of CIS patients experience some form of cognitive impairment (Potagas et al, 2008;Zipoli et al, 2010). This conclusion is in line with a systematic review by Anhoque et al (2010) stating that cognitive impairment in CIS seems to be less frequent and intense than in definite MS.…”
Section: Prevalence Of Cognitive Dysfunction and Impaired Processing supporting
confidence: 73%
“…In other work examining cognition early in the disease course, impairment has been reported to occur in 25-57%) of patients with probable MS or clinically isolated syndrome (CIS; Achiron & Barak, 2003;Feuillet et al, 2007;Potagas et al, 2008;Zipoli et al, 2010). CIS is the first episode of a demyelinating and inflammatory disease of the central nervous system and a proportion of CIS patients will later be diagnosed with definite MS (Anhoque, Domingues, Teixeira, & Domingues, 2010). The wide variability in prevalence of cognitive impairments across samples of patients with CIS is likely due to the different neuropsychological tests and criteria for defining impairment employed between the studies.…”
Section: Prevalence Of Cognitive Dysfunction and Impaired Processing mentioning
confidence: 99%
“…It was shown that the presence of such psychiatric comorbidities has a great impact in general health status and quality of life of MS patients [9][10][11] . However, little is known about these neuropsychiatric comorbidities in patients with CIS 12 . Some studies have found that neuropsychiatric symptoms in MS are related with the degree of functional disability and with disease duration 13,14 .…”
mentioning
confidence: 99%